Bone marrow mesenchymal stem cells differentiate into intestinal epithelioid cells through the ERK1/2 pathway - Ting Jiang,; Meng-lin Shi,; Geng Xia,; Yi-Na Yang,; Jia-Min Xu,; Yun-Jie Lei,; Ying-Mei Tang,; Jin-Hui Yang, (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Previous studies have found that the injection of rat bone marrow mesenchymal stem cells (rBMSCs) in a mouse model of acute hepatic failure significantly relieves intestinal damage and endotoxemia. However, the mechanism of this process remains unknown. This study demonstrated the differentiation of rBMSCs into enterocyte-like cells and possible molecular mechanisms for this with the aim of finding a new treatment for intestinal epithelial injury and endotoxemia during liver failure.Materials and Methods: rBMSCs were isolated from rat femurs and tibias. Differentiation was induced by co-culturing rBMSCs with rat intestinal epithelial cells (mIEC-6) using Transwell plates; after three, seven, and ten days of induction, expression of specific differentiation molecules were quantified. To inhibit the activity of the Mitogen-activated protein kinase 1/2 (ERK1/2) signaling pathway, an inhibitor of Mitogen-activated protein kinase kinase 1/2 (MEK1/2) was added to the co-culture medium, and western blot analysis was performed after 36 or 72 h to evaluate the expression of ERK1/2 signaling pathway markers (p-MEK1/2 and p-ERK1/2).Results: The rBMSCs differentiated into enterocyte-like cells when co-cultured with mIEC-6 cells. Inhibition of ERK1/2 signaling abrogated the activity of MEK1/2, but MEK increased after 72 h, and the epithelioid differentiation of rBMSCs was consistent with the change in MEK expression.Conclusion: rBMSCs differentiate into intestinal epithelium after co-culture with mIEC-6 by regulation of the ERK1/2 signaling pathway. Further research is needed to elucidate the network of mechanisms.Cite this article as: Jiang T, Shi ML, Xia G, et al. Bone marrow mesenchymal stem cells differentiate into intestinal epithelioid cells through the ERK1/2 pathway. Turk J Gastroenterol 2020; 31(6): 459-65.